Development of E-Module Based on the Traditional Puyuh Game on the Cooperation Character and the Tolerance of Elementary School Students - Syahrial Syahrial; Asrial Asria; Husni Sabil; Dwi Agus Kurniawan; Rahmat Perdana; Nurul Delima Kiska (Yayasan Keluarga Guru Mandiri, 2022)
Electronic modules provide convenience for teachers and students in learning activities. This study aims to determine the feasibility or validity of the electronic module based on the traditional game